Analisis Pendidikan karakter pada Pembelajaran Seni Budaya dan Prakarya (SBdP) di Kelas II SD Inpres 3 Talise - Jamila2305; Azizah; Yun Ratna Lagandesa (JURNAL DIKDAS, 2024)
This study aims to examine the implementation of character education in the teaching of Cultural Arts and Crafts (SBdP) as well as the character values applied to second-grade students at SD Inpres 3 Talise. The research uses a qualitative descriptive approach. The subjects consisted of 27 students, including 17 boys and 10 girls. Data collection techniques included observation, interviews, and documentation. Data were analyzed through data reduction, data presentation, and conclusion drawing. The results show that the implementation of character education in SBdP learning was quite optimal, guided by the Lesson Plan (RPP). The character values emphasized include religious, discipline, honesty, and creativity. Religious values were instilled through group prayers before lessons. Discipline was applied through attendance checks. Honesty was encouraged by having students complete assignments without cheating. Creativity was developed through activities such as singing the song "Lonceng Ayah" using improvised musical instruments made from surrounding objects. This study highlights the importance of integrating character education into SBdP learning to help shape students' personalities and positive attitudes from an early age.